Application of 3D printed teeth models in teaching conservative dentistry and endodontics - Dobroś-Zawadzka, Katarzyna (2022)
INTRODUCTION During their pre-clinical classes, the students carry out dental procedures on the Dental Patient Simulator (DPS) featuring the standard teeth models. Sometimes the extracted ones are also used. None of those teaching aids are free from disadvantages, however. Standard teeth models do not accurately reflect the actual anatomy of the teeth, do not feature the pulp chamber and roots, whereas the hardness of the material does not reflect the hardness of tissue. The extracted teeth, on the other hand, are notoriously hard to match in terms of specific types, and carry an obvious risk of cross-infection. Reports on an appreciable potential for making use of the three-dimensional (3D) models in teaching dental students emerged throughout the last decade. They predominantly focused on prosthodontics, and on dental surgery. Manifestly fewer studies addressed the use of the 3D teeth models in teaching restorative dentistry and endodontics. AIM 1) Based on the scoping review dedicated to assessing the current body of the knowledge on the use of 3D models in teaching dentistry. 2) The study aimed at designing and printing out an original 3D model of the mandible, including the teeth, in conjunction with the replication of carious lesions of different classes (according to Black’s classification), and of the pulp, as well as at addressing specific research questions put f
Keywords: root canal therapy; dental education; hands-on practice; three-dimensional printing